Evaluation of Neuron-Based Sensing with the Neurotransmitter Serotonin - Skeen, Rodney S.; Kisaalita, William S.; Van Wie, Bernard J.; Fung, Simon J.; Barnes, Charles D. (Biosensors and Bioelectronics, 1990)
Results are presented on the development of a novel biosensor which will use neurons or neuronal components as both the recognition elements and primary transducers for analyte quantitation. This concept is demonstrated and evaluated by exposing identified neurons from the visceral ganglia of the pond snail Limnea stagnalis to the model analyte serotonin. Experiments reveal a reversible, concentration-dependent increase in the rate of spontaneous action potential generation, over a concentration range of four orders of magnitude. Studies with the antagonist methysergide verify that this response is mediated through serotonin-sensitive receptors. Exposure of the neurons to serotonin causes the firing frequency to rapidly increase to a maximum and then slowly diminish to a sub-optimal level. It was found that the maximum frequency provides an indication of chemical concentration that is repeatable. Data are also presented which further advanced the field of neuronal biosensing by demonstrating both the effects of cell to cell variability on response reproducibility and the effects of the desensitizing response on the operation of a neuron-based sensor in both a continuous and discontinuous mode.